Professional learning of academics in HEIs; trying to navigate the tensions - Malamut, Jason (2015)
The academic identity is under attack. There are many tensions academics face; what does it mean to be an academic, how should they be developed and what effects performativity and managerialism have on them? The academic identity is based on personal values and also on the values of the department/discipline and HEIs (Higher Education Institutions). In trying to understand the nature of HEIs, we see what it is that academics do, which is to teach and research. Academia is a profession of prestige and of proving your knowledge. Intrinsic motivations play into how academics go about learning and improving their knowledge; this is mainly found in the disciplines themselves. Even with the best of intentions, professional development opportunities curated by the HEI don’t always seem in line with how academics work, as they find a ‘deficit’ model of professional development to infringe on their freedom, again, attacking their identity. Using performance indicators such as the REF (Research Excellence Framework) and NSS (National Student Survey) may also encroach on their identity, forcing academics to choose to focus between either research or teaching performance indicators and therefore detract time away from the other activity. This all calls into question the academics ability to develop and again ask, ‘What are academics for?’ This also raises the point that although performance management and managerialism may shape that identity, is it always a bad thing? Are there any positives to having academics accountable to the students and organization? Leaders should try to be mindful of how academics see themselves and the way they form the identities in the community and create learning opportunities that speak to those values to help promote academic learning. I have chosen to undertake this study as I have keen interest in professional development and learning. The literature on this subject matter is not extensive, and therefore this study pulls from a variety of sources in order to paint a clearer picture. This study is based on some of the concepts that I have uncovered in my previous assignment as well as the literature and through a mix-methods design, I present interview and survey data to back-up the claims made. The first section looks at what it means to be an academic, followed by how it is academics learn and finally performativity and managerialism. The following section addresses the methodological approach for the study, after which I will present the collected data. I then present my analysis and conclusion. I have included an issues portion to my methodology section to highlight some of the challenges I faced while trying to obtain participants as well as relevant data. The analysis section also has a further considerations paragraph which talks about the potential for a follow-up study.